Geochemistry of the Dissolved Load of the Ramganga River, Ganga Basin, India: Anthropogenic Impacts and Chemical Weathering - Khan, Mohd Yawar Ali; Panwar, Sugandha; Wen, Jie (Frontiers in Environmental Science, 2022)
The Ramganga basin is an important sub-catchment of the Ganga River to study the wide-scale effects of human-induced changes on geochemical processes. The basin inhabits pristine locations in the upstream and dense human establishments in the floodplain region. Further, the entrapment of upstream sediments in the Kalagarh dam aids in creating different geochemical regimes. To reveal the geochemical heterogeneity over the multi-spatial and temporal scale, controlling factors (natural and anthropogenic), and source endmembers, dissolved load samples were collected during the pre-monsoon, monsoon, and post-monsoon season of the year 2014. Major cations and anions data were analyzed using Principal Component Analysis (PCA) and mass-balancing equations based forward modelling to quantify the contribution from the atmosphere, rock weathering, and anthropogenic sources. The results show chemical weathering predominates the dilution effect during the post-monsoon season. A high level of pollution prevails during the non-monsoon season and particularly in floodplain tributaries. Anthropogenic sources contribute up to 41% of the dissolved load composition, whereas silicate and carbonate weathering predominantly contributes 93% and 82% of the dissolved load. The silicate weathering rate (5.04 t km−2 y−1) is higher than the carbonate weathering rate (4.3 t km−2 y−1) and efficiently uptake 3.6 × 105 mol km−2 y−1 of CO2. The findings will reveal the extent of geochemical heterogeneity and controlling factors influencing the element flux, weathering rates, and chemical transportation over multi-spatial scales.